Impurity-Related Nonlinear Optical Absorption in Delta-Doped Quantum Rings (2014)
ABSTRACT: Using a variational procedure within the e ective mass approximation, we have calculated the hydrogenic impurity binding energy as well as the impurity-related nonlinear optical absorption in a single quantum ring with axial n-type delta-doping. The delta-like potential along the z-direction is analytically modeled with a Hartree-like con ning pro le tted to a one-dimensional Thomas Fermi-based potential in the local density approximation. Both on-center and on-edge impurity positions are considered and the energies of the impurity states are examined as functions of the vertical size of the ring. It is found that the e ect of changes in the geometry of the quantum ring leads to a shifting of the resonant peaks of the intra-band optical spectrum.